(untitled) (LEARNing Landscapes, 2010)
Sheila Watt-Cloutier grew up in Kuujjuaq, a small village in Northern Quebec. In this interview she relates how growing up in a traditional Inuit hunting culture gave her a deep sense of connection—an essential element for the work she does today as a climate change awareness advocate. She applauds the environmental efforts of individuals at the grassroots level but feels very strongly that governments and policymakers must come on board to effect true, lasting change. She believes that our educational system has a key role to play in helping to reduce climate change and she is encouraged to see young people becoming "natural"conservationists. She says that the future of education lies in providing a more holistic approach so that people can develop this sense of connection with a focus on humanity and sustainability instead of just economics. Finally, she offers a quick preview of what to expect in her upcoming book.